Advances in sweat-activated batteries for powering wearable electronics: structures, materials, challenges, and perspectives - Yu Yuan; Yile Lu; Tianyue Liang; Haowei Jia; Linghui Meng; Yanzhe Zhu; Jinbo Wang; Tianxu Huang; Peiyuan Guan; Lu Zhou; Yingze Zhou; Zhi Li; et al. (JPhys Energy)
Flexible wearable devices have gained increasing attention in the field of health and fitness monitoring because of their biocompatibility and ability to collect biomarkers seamlessly and instantly. Consequently, a new research direction has emerged on how to power these portable electronic devices. Currently, the majority of wearable electronic devices are powered by lithium-ion batteries (LIBs). However, owing to safety concerns and the bulky size of LIBs, there is a growing demand for sustainable, light, and wearable power supplies. Thus, sweat-activated batteries (SABs) were recently proposed as a source of power generation and energy storage. To validate the feasibility of using SABs to power wearable devices, we briefly recalled the history of the development of SABs in recent years, as well as the present research outcomes. This review overviews three categories of SABs (conventional-redox batteries, metal-air batteries, and others), which based on two anode materials (Magnesium and Zinc) and the working mechanism of diverse categories was interspersed throughout the discussion. Moreover, the electrolytes in SABs and suitable substrates for integrating batteries into wearable devices are thoroughly discussed. Furthermore, various SAB application scenarios are reviewed. This comprehensive review will not only offer insights into the current state of SABs technology but also provide valuable guidance and suggestions for future advancements and applications in this field.